The Effect of Video-Based Pedagogy on Students’ Spatial Ability in Solid Geometry - Asiamah, Osmond A; Fletcher, Jonathan A (Asian Journal of Interdisciplinary Research, 2023)
This study explored the effect of video-based pedagogy on students’ spatial ability in solid geometry, in the Birim Central Municipality of Ghana. A mixed methods concurrent triangulation research design was employed. The same treatment and methodologies were used on two intact classes (n=43 and n=39 respectively) of the two study schools. Descriptive statistics was used to analyse the questionnaire data, whereas data reduction technique and content analysis were used to analyse the interview reports and written test scripts data. The two separate data sets produced similar results, with the qualitative results confirming the quantitative results. The findings reveal that video-based pedagogy significantly promotes students’ 2D and 3D spatial ability, and fosters students-centered learning in solid geometry. The results also provide evidence and recommendations on the significance of video-based pedagogy in improving students’ mathematical understanding at the Senior High School level.